2008
DOI: 10.1104/pp.108.126979
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Mature Arabidopsis Trichomes Reveals That NOECK Encodes the MIXTA-Like Transcriptional Regulator MYB106    

Abstract: Leaf hairs (trichomes) of Arabidopsis (Arabidopsis thaliana) have been extensively used as a model to address general questions in cell and developmental biology. Here, we lay the foundation for a systems-level understanding of the biology of this model cell type by performing genome-wide gene expression analyses. We have identified 3,231 genes that are up-regulated in mature trichomes relative to leaves without trichomes, and we compared wild-type trichomes with two mutants, glabra3 and triptychon, that affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
230
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(244 citation statements)
references
References 87 publications
14
230
0
Order By: Relevance
“…The ubiquity of reporter expression under the control of the AtXYL1 promoter at the organ level is also reflected in published genome-wide microarray analyses (Schmid et al, 2005;Jakoby et al, 2008). Cell type-specific studies confirm the expression of AtXYL1 in guard cells and trichomes as well as a lack of expression in pollen (Pina et al, 2005;Jakoby et al, 2008;Yang et al, 2008). The expression pattern revealed by the promoter-reporter fusion is remarkably similar to that of MUR3, a galactosyltransferase involved in xyloglucan synthesis (Madson et al, 2003).…”
Section: Regulation Of A-xylosidase Activitymentioning
confidence: 76%
See 1 more Smart Citation
“…The ubiquity of reporter expression under the control of the AtXYL1 promoter at the organ level is also reflected in published genome-wide microarray analyses (Schmid et al, 2005;Jakoby et al, 2008). Cell type-specific studies confirm the expression of AtXYL1 in guard cells and trichomes as well as a lack of expression in pollen (Pina et al, 2005;Jakoby et al, 2008;Yang et al, 2008). The expression pattern revealed by the promoter-reporter fusion is remarkably similar to that of MUR3, a galactosyltransferase involved in xyloglucan synthesis (Madson et al, 2003).…”
Section: Regulation Of A-xylosidase Activitymentioning
confidence: 76%
“…5), appears to be widespread, as would be expected for the only a-xylosidase active against xyloglucan. The ubiquity of reporter expression under the control of the AtXYL1 promoter at the organ level is also reflected in published genome-wide microarray analyses (Schmid et al, 2005;Jakoby et al, 2008). Cell type-specific studies confirm the expression of AtXYL1 in guard cells and trichomes as well as a lack of expression in pollen (Pina et al, 2005;Jakoby et al, 2008;Yang et al, 2008).…”
Section: Regulation Of A-xylosidase Activitymentioning
confidence: 80%
“…5 and SI Methods). In our model, a mitotic cycle is converted into an endocycle through a developmentally controlled (trichome specification) wave of the presumptive CDK inhibitor SIM, completely blocking M-phase CDK activity during further trichome development; this takes into account that SIM is a direct target of the trichome specification machinery and one of the highest expressed genes in trichomes (45,46). It should be noted that moderate levels of SIM or related inhibitors might also be used in plants to delay the M-phase CDK activity and, by that, to establish a G2 phase (44).…”
Section: Resultsmentioning
confidence: 99%
“…1a) [17]. We also performed a comparative analysis of aquaporin expression between mature pollen (MP) [7] and single cell types such as trichome cells (TC) [18], mesophyll cells (MC) [19], stomatal guard cells (GC) [19] and lateral root cap stage I (LRC) used as a representative of the transcriptomic analysis obtained for three developmental stages in five different domains of Arabidopsis root [20]. We found that trichome cells (TC), mesophyll cells (MC), stomatal guard cells (GC) and lateral root cap cells stage 1 (LRC), or any other root cell type (data not shown), all expressed a larger number of aquaporin genes (13, 13, 14 and 17, respectively) compared to Arabidopsis mature pollen grains that only expressed 6 (Fig.…”
Section: Resultsmentioning
confidence: 99%